CULTURAL SPECIFICITY IN NON-VERBAL COMMUNICATION (International Conference on Modern Science and Scientific Studies, 2025)
This thesis explores the cultural dimensions of non-verbal communication and how different nations use and interpret non-verbal cues such as gestures, facial expressions, body language, eye contact, and proxemics. The research emphasizes the importance of understanding national differences in non-verbal behavior to enhance intercultural communication and avoid misunderstandings